Dari Tazkiyah al-Nafs menuju Sufisme Digital: Negosiasi Pendidikan Spiritual bagi Generasi Z dan Alpha dalam Pendidikan Islam Kontemporer di SMPI Miftahul Iman - Octa Salman Rhamdani (Yayasan Abdurrauf Cendekia Nusantara, 2026)
Islamic education requires a balance between the outward dimension associated with Sharia and moral conduct and the inward dimension related to Sufism, with the aim of cultivating individuals who possess deep spiritual awareness (ihsan). The emergence of Generation Z and Alpha, who grow up within a digital ecosystem, presents new challenges to the internalization of contemplative values such as tazkiyah al-nafs. A digital lifestyle characterized by technological dependence, short attention spans, and a preference for instant gratification often contrasts with the reflective practices and patience that constitute the essence of Sufi education. This study aims to analyze the strategies, challenges, and obstacles in instilling moral and Sufistic values among digital generations at SMPI Miftahul Iman. The research employs a qualitative descriptive approach, with primary data obtained through in-depth interviews with Islamic Religious Education teachers, observations of religious activities at the school, and analysis of supporting documents. The findings reveal that the school implements two main strategies: integrating Islamic Religious Education with interactive digital media to enhance student engagement and cultivating consistent religious habits in which teachers act as uswah hasanah (exemplary role models). The major challenges arise from the generational gap between students’ digital culture—characterized by social validation and immediacy—and the Sufi values that emphasize tranquility, reflection, and patience. Institutional constraints, including a curriculum that remains largely theoretical and limited teacher competence in Sufism, also constitute significant barriers. Despite these challenges, the initiatives demonstrate positive impacts on students’ behavioral changes, particularly in disciplined worship practices and social responsibility. This study highlights the importance of recontextualizing Sufi education through a “digital Sufism” approach as a strategy to strengthen the spiritual resilience of young generations amid the distractions of digital culture. [Pendidikan Islam menuntut keseimbangan antara dimensi lahiriah yang berkaitan dengan syariat dan perilaku moral dengan dimensi batiniah yang berhubungan dengan tasawuf, dengan tujuan membentuk individu yang memiliki kesadaran spiritual mendalam (ihsan). Perkembangan Generasi Z dan Alpha yang tumbuh dalam ekosistem digital menghadirkan tantangan baru bagi proses internalisasi nilai-nilai kontemplatif seperti tazkiyah al-nafs. Pola kehidupan digital yang ditandai oleh ketergantungan pada teknologi, rentang perhatian yang pendek, serta kecenderungan pada kepuasan instan sering kali tidak sejalan dengan praktik reflektif dan kesabaran yang menjadi inti pendidikan tasawuf. Penelitian ini bertujuan menganalisis strategi, tantangan, dan hambatan dalam penanaman nilai-nilai akhlak dan tasawuf kepada generasi digital di SMPI Miftahul Iman. Penelitian menggunakan pendekatan deskriptif kualitatif dengan sumber data utama yang diperoleh melalui wawancara mendalam dengan guru Pendidikan Agama Islam, observasi terhadap aktivitas keagamaan di sekolah, serta analisis dokumen pendukung. Hasil penelitian menunjukkan bahwa sekolah menerapkan dua strategi utama, yaitu integrasi pembelajaran Pendidikan Agama Islam dengan media digital interaktif untuk meningkatkan keterlibatan siswa serta pembentukan kebiasaan religius yang berkelanjutan dengan guru berperan sebagai uswah hasanah. Kendala utama yang dihadapi berkaitan dengan kesenjangan generasi antara budaya digital siswa yang menekankan validasi sosial dan kecepatan respons dengan nilai-nilai tasawuf yang menuntut ketenangan, refleksi, dan kesabaran. Selain itu, keterbatasan kurikulum yang masih bersifat teoritis serta kompetensi guru dalam kajian tasawuf juga menjadi hambatan institusional. Meskipun demikian, upaya yang dilakukan menunjukkan dampak positif terhadap perubahan perilaku siswa, terutama dalam kedisiplinan beribadah dan tanggung jawab sosial. Penelitian ini menegaskan pentingnya rekontekstualisasi pendidikan tasawuf melalui pendekatan digital sufism sebagai strategi untuk memperkuat ketahanan spiritual generasi muda di tengah distraksi budaya digital.]